2011
DOI: 10.1097/ccm.0b013e3182282bbe
|View full text |Cite
|
Sign up to set email alerts
|

Active rehabilitation and physical therapy during extracorporeal membrane oxygenation while awaiting lung transplantation: A practical approach*

Abstract: A comprehensive, multidisciplinary system can be developed to safely allow for active rehabilitation, physical therapy, and ambulation of patients being managed with extracorporeal membrane oxygenation. Such programs may lead to a decreased threshold for the utilization of extracorporeal membrane oxygenation before transplant and have the potential to improve conditioning, decrease resource utilization, and lead to better outcomes in patients who require extracorporeal membrane oxygenation before lung transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 14 publications
1
165
1
1
Order By: Relevance
“…10 Several centers use ambulatory ECMO to rehabilitate patients to mitigate deconditioning in an attempt to improve outcomes in these critically ill patients. [11][12][13][14][15] Early studies demonstrated feasibility and potentially improved outcomes with this ECMO rehabilitation strategy as a bridge to transplantation. 14,16,17 In a single-center study, subjects who were spontaneously breathing while supported with ECMO had better 1-y survival rates post-transplant than did their mechanically ventilated counterparts who were supported with ECMO and proceeded to lung transplantation.…”
Section: See the Related Editorial On Page 117mentioning
confidence: 99%
“…10 Several centers use ambulatory ECMO to rehabilitate patients to mitigate deconditioning in an attempt to improve outcomes in these critically ill patients. [11][12][13][14][15] Early studies demonstrated feasibility and potentially improved outcomes with this ECMO rehabilitation strategy as a bridge to transplantation. 14,16,17 In a single-center study, subjects who were spontaneously breathing while supported with ECMO had better 1-y survival rates post-transplant than did their mechanically ventilated counterparts who were supported with ECMO and proceeded to lung transplantation.…”
Section: See the Related Editorial On Page 117mentioning
confidence: 99%
“…Although it is impossible to refute this approach outright, more recent analyses of data sets with propensity score matching indicate that survival for children on ECMO at the time of transplant may not be significantly different than those who do not require ECMO. Moreover, the earlier literature characterized by poor outcomes predates the development of centrifugal pumps, miniaturized ECMO circuits, and general movement from venoarterial to VV ECMO configurations which are all potentially associated with fewer ECMO related complications (1,3,5,7). NCH offers ECMO as bridge to transplant for local patients, most of whom have cystic fibrosis, when critical illness occurs in previously-listed patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of pediatric transplant and the development of more reliable longerterm support devices (such as miniaturized ECMO circuits, centrifugal pumps, and ventricular assist devices) the prior resistance to use ECMO to support irreversible organ failure is increasingly being reconsidered. Use of ECMO to bridge patients to lung transplantation is increasingly being done at transplant centers (1)(2)(3)(4)(5)(6)(7). For these reasons, pediatric ECMO centers are finding themselves supporting patients with irreversible heart and/or lung failure for whom organ transplantation is a potentially life-saving intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most illustrative of the safety of early mobilization, a case series by Turner et al [23] studied early mobilization as part of a rehabilitation program for patients requiring extracorporeal membrane oxygenation (ECMO) support as a bridge to lung transplantation. In the patients requiring ECMO in this series, they reported no adverse events and it has become commonplace at our own institution to aggressively mobilize patients who require mechanical circulatory support.…”
Section: Safety and Feasibilitymentioning
confidence: 99%